Giovanni Anceschi and the Theory of Schematic Representation. Drawing as a Graphic Language (diségno, 2025)
The article aims to recount the evolution of Giovanni Anceschi's research work on the subject of visual design, specifically with regard to schematic representation modes and processes of depiction. The value of drawing as a visual language and graphic instrument was one of the cornerstones of Anceschi's theoretical reasoning. Specifically, we intend to start from his degree thesis of 1966 at the Department of Visual Communication at the Hochschule für Gestaltung in Ulm (under the supervision of Abraham Moles, Tomás Maldonado and Herbert Kapitzky), passing through the partial translation that the author himself offers in the 1981 collection ‘Progettazione visiva’, up to the seminal text of 1992 entitled ‘L'oggetto della raffigurazione’. By means of a philological reconstruction of the publications in which Anceschi insisted on these themes, the aim is to investigate how the graphic designer's point of view interprets concepts proper to drawing such as schematisation or representation, and how these themes can inform the theoretical debate on graphic design.
Keywords: graphic language; drawing; graphic design; Giovanni Anceschi; design